Preparation and evaluation of antibacterial mupirocin cream emulsion using cocamidopropyl betaine emulsifier - Gangurde, Avinash B; Pagar, Suraj (Journal of Applied Pharmaceutical Research, 2024)
Background: This study aimed to develop and evaluate an antibacterial cream emulsion containing mupirocin using Cocamidopropyl betaine (CAPB) as an emulsifier. Mupirocin, a topical antibiotic effective against Staphylococcus aureus (including methicillin-resistant strains), was formulated into a cream to enhance its topical delivery. Materials and Methods: Mupirocin cream emulsion formulations were developed with varying concentrations of CAPB, PEG-400, and glycerol monostearate. The cream formulations were mainly evaluated for in vitro diffusion tests, antibacterial activity tests, and stability studies. Result and Discussion: CAPB produced a stable cream emulsion formulation (F7) at 30% concentration and 2% PEG-400. The formulation (F7) exhibited sustained drug release over 3.5 hours in the diffusion test. The formulation F7 showed a higher zone of inhibition, 32.16±2.2 mm, than the marketed mupirocin cream, 29.56±1.35 mm, for the Staphylococcus aureus strain. The prepared cream formulation F7 was found stable over 90 days at different temperature conditions (8±2°C, 25±2°C and 40±2°C). Conclusion: The study concludes that CAPB effectively enhances mupirocin cream solubility and antibacterial properties, making it a promising option for treating bacterial skin infections.